HEMOGLOBIN INDICATORS OF CARP FISH - Khurramova S.G.; Kupalova S. B.; Kurbanov F. E. (Bright Mind Publishing, 2025)
During the experiments, it was noticed that the hematological parameters of one-year-old carp (fingerlings) raised on a fish farm have different indicators depending on the type of pond contained.Keyword. The difference in the average size of erythrocytes in fish raised under intensive technology, pool conditions, is 19.2; 47.35 microns less than in the experiments, and this indicator was found in extensive technology and conditions of an artificial pond, and 34.6 - in the corresponding cultivation; It was found that the average size of erythrocytes is 57.3 microns.
Keywords: Erythrocyte, 1012/l, Hemocrit, Amount of hemoglobin in an erythrocyte, pg, Average size of an erythrocyte, μm, Leukocyte x1012/l, Extensive technology, Intensive technology, Artificial pool, Hemoglobin in pool conditions, Confined water pool.